Leveraging Educational Functions of Inspirational Video: Emerging Students’ Sense of Community Development - Adi Suryani; Soedarso Soedarso; Zainul Muhibbin; Marsudi Marsudi; Ni Wayan Suarmini (Universitas Teuku Umar, 2020)
Today, the use of video is prevalent in facilitating learning process. Commonly, it is used to deliver cognitive content. By using video, knowledge the delivered content can be easier to understand, clearer to grasp and becomes more interesting. Many studies devoted to explore the cognitive functions of video. However, how video can affectively contribute to self-development and potential community developed remains unexplored widely. This study intends to examine inspirational video impacts on students’ analysis, inspiration and motivation to develop themselves and contribute their self-development to wider community. The study adopts a qualitative method. The data are collected from thirty-eight student participants. The study finds that video can stimulate the student-participants to develop self-commitment to undertake self-learning, perseverance, hard work, diligence, emotion regulation and elf-efficacy. The study also reveals that the student participants develop commitment to contribute their learning to community development. Thus, it can be indicated that video is a potential development tool, which can promote human capital improvement through self-learning and self improvement and social capital, through social cohesion and engagement for succeeding community development.